Teaching International Politics in High School - Ethics and Public Policy Center, Washington, DC.; English, Raymond; Ethics and Public Policy Center, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1989)
Approaches to teaching about international politics and avenues to peace should be realistic and pragmatic rather than based on generalities about global education and peace education. This volume contains essays on international economic relations, cultural and linguistic understanding, and the conflict of ideologies and value systems in international affairs. The 13 essays included are: "America, the World, and Our Schools" (W. J. Bennett); "International Politics and Global Education" (M. A. East); "The Realities of Foreign Policy Making" (J. P. Roche); "The New Look in Social Studies" (R. H. Wilson); "Trading States or Territorial States?" (J. L. Tucker); "Avoiding the 'isms'" (R. L. Hayden); "A State Project in International Studies" (M. Hartoonian); "Global Education: An Ambiguous Innovation" (R. English); "Peacekeeping in the Nuclear Age" (K. B. Payne; J. Coleman); "National Security in the Nuclear Age" (J. E. Harf); "Teaching about the United Nations" (J. G. Pilon); "A Critique of 'Peace Education'" (T. B. Smith); and "The Historian-Filmmaker" (P. C. Rollins; R. T. Baird). Appendices contain sample textbook pages as well as a glossary, maps, theories of international politics, and an international timeline from 1945 to the present. (JB)
Availability: University Press of America, Inc., 4720 Boston Way, Lanham, MD 20706 ($14.75).
Teachers.
Practitioners.
Microfiche.
Keywords: Civics; Controversial Issues (Course Content); Disarmament; Documentaries; Foreign Policy; Global Approach; High Schools; Instructional Materials; International Relations; International Studies; Modern History; National Security; Nuclear Warfare; Peace; Secondary School Curriculum; World Affairs; United Nations; Books; Guides, Non-Classroom.; Opinion Papers